Perubahan Sosial Masyarakat Akibat Konversi Minyak Tanah Ke LPG di Kelurahan Tanjungpinang Barat - Suciati, Indrati Sri; Suryaningsih; Solina, Emmy (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2017)
Social changes are any changes in social institutions within a society, which affect the social system, including the values, attitudes and behavior patterns among groups in society. Pressure on the definition is the basic set of social institutions as human beings, the changes which then affect other social systems. Based on preliminary observations of this LPG conversion program apparently was sudden and unplanned comprehensively. Framework will be operationalized concept refers to the opinion Selo Soemardjan and Bertrand which state that social change affects the social system, where the elements of the social system, namely beliefs, feelings and thoughts, goals, rules / norms, status/ role and facilities. Qualitative research with a qualitative descriptive design format, which aims to describe, to tell a variety of conditions, situations and phenomena of social realities that exist in society. Sampled data were collected through interviews with informants as many as 14 people. From the research results can be concluded that the kerosene to LPG in the Village of West Tanjungpinang has given the change to more efficient public spending among others so survival is more assured, the pattern of behavior among members of the public is more awake, environmental sustainability is maintained by the reduction of air pollution so as to create of a society that is more practical, efficient and effective